2020
DOI: 10.1002/1348-9585.12152
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Japanese version of the CDC HRQOL-4 in workers

Abstract: Background We set out to investigate the reliability and validity of the Japanese version of the CDC core healthy day measures assessing health‐related quality of life (CDC HRQOL‐4) in Japanese workers. Methods This cross‐sectional study was conducted among 1360 Japanese workers of one Japanese company located in Kyushu. Cronbach's alpha was calculated to evaluate the internal consistency of CDC HRQOL‐4 items. The concurrent validity was tested by assessing whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Psychosocial conditions were examined through assessment of health-related quality of life (HRQOL), K6[15], and loneliness. HRQOL was measured using the CDC HRQOL-4[16,17], which was originally developed by the US Centers for Disease Control and Prevention. Health-related items included medical history, treatment interruptions, back pain, and stiff shoulders.…”
Section: Methodsmentioning
confidence: 99%
“…Psychosocial conditions were examined through assessment of health-related quality of life (HRQOL), K6[15], and loneliness. HRQOL was measured using the CDC HRQOL-4[16,17], which was originally developed by the US Centers for Disease Control and Prevention. Health-related items included medical history, treatment interruptions, back pain, and stiff shoulders.…”
Section: Methodsmentioning
confidence: 99%
“…A Japanese version of the CDC HRQOL-4 has also been developed, and several previous studies have been conducted on Japanese workers using the same. 15,16 Previous studies have reported that the Japanese version of the HRQOL shows good concurrent validity with the Short Form-8 (SF-8 Form), a widely used indicator of HRQOL in Japan and the work functioning impairment scale (WFun), an indicator of the worker’s functional disability at work due to health problems which has good construct validity among Japanese workers. 15 The forward translations were reconciled.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Previous studies have reported that the Japanese version of the HRQOL shows good concurrent validity with the Short Form-8 (SF-8 Form), a widely used indicator of HRQOL in Japan and the work functioning impairment scale (WFun), an indicator of the worker’s functional disability at work due to health problems which has good construct validity among Japanese workers. 15 The forward translations were reconciled. After that, the back translation was performed by a native English-speaking researcher to ensure the equivalence between the original English version and the Japanese translated version.…”
Section: Methodsmentioning
confidence: 99%
“…Self-rated health was recorded as excellent, very good, good, fair, or poor [19]. We used the Japanese version of the CDC HRQOL-4 developed by Japanese epidemiologists and occupational physicians [17].…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, the Japanese version of the CDC HRQOL-4 was developed, and evaluated for its reliability and validity for use with workers [16]. Furthermore, because the CDC HRQOL-4 was found to be associated with indicators of work functioning impairment [17], the measurement of HRQOL is helpful for both health and labor-management assessment of workers.…”
Section: Introductionmentioning
confidence: 99%